What factors determine treatment outcome in aneurysmal subarachnoid hemorrhage in the modern era? A post hoc STASH analysis - Teo, M; Guilfoyle, MR; Turner, C; Kirkpatrick, PJ; Kirkpatrick, PJ; Turner, CL; Murray, GD; Hutchinson, PJ; Teasdale, G; Murray, GD; Kirkpatrick, PJ; Mendelow, AD; et al. (Elsevier, 2017)
Background The management of aneurysmal subarachnoid hemorrhage (aSAH) has changed dramatically in the last few decades with the publication of a few major studies, including ISAT (International Subarachnoid Aneurysm Trial, the International Cooperative Study on the Timing of Aneurysm Surgery Study). The aim of this study is to analyze the outcome of patients with aSAH based on a contemporary series, identify the risk factors for poor outcome, and focus on patients with good-grade aSAH (to match the ISAT cohort). Methods Baseline demographic and outcome data (modified Rankin Scale) were available for the 803 patients recruited from the STASH (Simvastatin in Aneurysmal Subarachnoid Haemorrhage) trial for post hoc analysis, using a χ2 test or 2-sample t test. Logistic regression analysis was performed to assess the risk factors for poor outcome at 6 months. Propensity matched analysis comparing coiling and clipping, and subgroup analysis of good-grade patients (World Federation of Neurosurgical Societies grade I–II) were also performed. Results Logistic regression analysis showed that the treatment modality (i.e., coiling or clipping) was not associated with poor outcome at 6 months (P = 0.839). The risk factors associated with poor outcome at 6 months were poor admission World Federation of Neurosurgical Societies grade (P < 0.0001), Fisher grade on initial computed tomography scan (P = 0.013), and the development of delayed cerebral ischemia (P < 0.0001). Subgroup analysis for good-grade patients only showed that 82% of patients after coiling and 78% of patients after clipping were classed as good outcome at 6 months (P = 0.181). Conclusions In the current era of aSAH management, apart from patients' admission status, SAH blood load and the development of delayed cerebral ischemia, treatment modality with either coiling or clipping was not associated with poor outcome difference at 6 months.